Human‐centred design thinking and public health education: A scoping review - Romero, Vivian; Donaldson, Holly (Health promotion journal of Australia, 2024)
Issue Addressed Human‐centred design thinking (HCDT) is gaining traction to develop appropriate public health interventions. The HCDT process helps frame problems with intention and encourages experimentation through collaboration. Public health graduates need an expanded toolkit to solve both the complex known problems of today, and the adaptability to solve the unknown problems of tomorrow. But how is the health promotion workforce being prepared with this innovation capability? This scoping review aims to provide a pedagogical understanding of teaching HCDT in public health education. Methods The Arksey & O'Malley framework is used to structure this review. Peer‐reviewed articles written from 2000 to 2023 across eight databases were analysed. The data extracted included: author/year, setting, aim/purpose, participants, HCDT framework, HCDT methods, outcomes and challenges. Results Nine relevant publications were included from a total of 208 records. The first reported use of HCDT in public health and health promotion teaching was in 2015. Teaching inspiration drew from established HCDT frameworks: d.school and IDEO which promote the iterative process of empathy/inspiration, ideation and testing/implementation. Conclusions HCDT has been used for both designing public health curricula and for teaching students to apply it in their practice. First, HCDT methods can be used to problem‐solve teaching and learning issues such as creating inviting learning environments and designing an HCDT unit. Second, the teaching of HCDT can prepare and equip the public health workforce to solve problems requiring tailored solutions from an empathetic and iterative stance working as a team. The teaching and practice of HCDT exemplifies the process of social innovation in health promotion. So What? As an emerging field, future studies and applications should include clarifying and evaluating the HCDT stages used. More publications will enable a fuller understanding and potentially advocate the necessity of teaching and learning HCDT in public health and health promotion.